PROJETO URBANO SUSTENTÁVEL PARA O CENTRO DE ITU - Ximenes, Deize (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article is the result of a research developed in the city of Itu - in the interior of the state of São Paulo, which had a disorderly expansion and an urban dispersion linked to real estate speculation and the inadequate use of natural resources. New scenarios were proposed for the development of a sustainable urban project for Itu, creating a connection between the Old Center and the New Center, starting from three structuring axes: ecological, cultural and hydrous, through sustainable mobility and territorial planning the Historic Center. The intention is to promote a better quality of urban life, a valorization and appropriation of green areas and architectural ensembles of historical importance for public use, and the preservation and rational use of natural resources available in the urban environment.